Efficiency of monoterpene compounds for control of rice pest Pomacea canaliculata - Printrakoon, Cheewarat; Bullangpoti, Vasakorn (Agriculture and Natural Resources, 2021)
Pomacea canaliculata (golden apple snail) is one of the most destructive and invasive rice pests in Southeast Asia and Thailand. This work focused on the molluscicidal efficiency of thymol, eucalyptol, and linalool against P. canaliculata under laboratory conditions. All essential oils made the snail motionless, closed its operculum shell, turned the soft body at the spire reddish and typically caused death within 24 hr. The toxicity levels of P. canaliculata after being exposed to the three essential oil compounds were significantly (p < 0.05) different at both 24 hr and 48 hr, with thymol being the most effective control (dose required for 50% mortality after 24 hr = 20.7 mg/L). Snails treated with thymol seemed to relax before death, with some typically recovering within 48 hr. The percentage of egg hatching in the treatment group (28.89–48.84%) was significantly (p < 0.005) reduced compared to the control (87-88%), with thymol being the most effective inhibitor (percentage of egg hatching = 28.89%). Glutathione-s-transferase (GST) and acetylcholinesterase (AChE) activities were reduced after snails were exposed to all three compounds (p < 0.05; correlation factor approximately1.25–1.50-fold and 1.64–2.14-fold for GST and AChE, respectively). However, carboxylesterase reduced only linalool and thymol. The findings indicated that all three essential oil compounds were viable alternatives to chemicals for controlling P. canaliculata.